Application of the Benefits of E-Commerce for Entrepreneurs - Nabila Salsahbilah; Zuhrinal M. Nawawi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
With the existence of E-Commerce, business owners or companies do not need to incur excessive costs in providing many stores and many employees. The purpose of this research is to find out how to apply the benefits of E-Commerce for entrepreneurs. The research method used is using qualitative methods. Where the qualitative research used is a literature study using books and other literature such as magazines, articles, journals, and trusted websites. The results of this study are the use of E-Commerce sometimes still requires other media, to realize a transaction. The use of E-Commerce is relatively easier for entrepreneurs with the condition that the contact on their mobile is a demand for the products offered. Marketing by utilizing E-Commerce for management and business managers can be managed by utilizing E-Commerce, so customers will be very loyal beyond loyalty to a business that is run offline.